Processo de trabalho e riscos ocupacionais dos profissionais de saúde bucal do Ceará na 1a e 2a onda da pandemia de COVID-19 - Silva, Raul Anderson Domingues Alves (2023)
The pandemic caused by the new coronavirus affected occupational practice in oral health. The aim of the study was To evaluate the work process of oral health professionals in Ceará in the 1st and 2nd wave of the COVID-19 pandemic. It was conducted in two stages with different methodological approaches. The first, a cross-sectional study, used secondary data collected by the Coordenadoria de Atenção à Saúde do Ceará in May 2020. Variables related to training, professional performance, and the work process during the pandemic were analyzed using the Statistical Package for the Social Sciences (SPSS) with a 95% confidence level. Factors such as longer time of training (RP=1.9; p=0.016); permanent employment relationship (RP=1.8; p=0.011), not receiving full personal protective equipment (PPE) (RP=1.8; p=0.009) were associated with a higher level of insecurity, while working in secondary health care (RP=0.5; p=0.039) with a lower level. The professionals who most reported not receiving complete PPE were oral health technicians and assistants (RP=2.1; p=0.001) and those who worked outside the capital and metropolitan area (RP=5.3; p<0.001). The second part, a case-control study, was composed of 91 dental surgeons (DC) notified with COVID-19 by e-SUS (cases) and 196 DCs who did not test positive during the evaluated period (controls), matched by sex and infection period (1st and 2nd wave). Data were collected through an online questionnaire composed of 3 blocks: sociodemographic, occupational, and behavioral factors outside the work environment, and analyzed in SPSS by a bivariate analysis and a logistic regression model, considering a 95% confidence interval. The risk factors identified were: The risk factors identified were: being 40 years of age or older (OR=3.14; p=0.005); being overweight (OR=2.13; p=0.020); not seeing patients with suspected or confirmed COVID-19 (OR=3.19; p=0.004); working in Primary Health Care in the public service (OR=5.17; p=<0.001); having a workload greater than 40 hours per week (OR=2.62; p=0.028) and not working in group practice (OR=2.76; p=0.007); having had contact with person with COVID-19 outside work (OR=2.75; p=0.006); not having taken the vaccine for COVID-19 or having an incomplete vaccination scheme (OR=3.84; p=0.005), and using adequate PPE (OR: 0.37; p=0.008) was considered a protective factor. It is concluded that the professionals acted in a situation of job insecurity in the first wave of the pandemic. Sociodemographic, occupational, and behavioral factors were established as risk and protective factors for COVID-19. Recognizing of these factors is necessary for improvements in protective measures for these professionals.